Construction machinery hire rates deviation in Malaysia: an inflation rate effect analysis - Musarat, M.A. (Pontificia Universidad Catolica de Chile, Escuela de Construccion Civil, 2021)
Machinery has been used in the construction industry in both small- and large-scale projects for a long time. Machinery is one of the main resources of any construction projects and rates deviation within the hiring of the machinery can result in cost overrun of the project. This study has been conducted to deal with the issue of deviating the machinery hire rates in the construction industry. The study accesses the machinery hire rates and aims to investigate the percentage deviation from 2013 to 2018. In this regard, statistical analysis was conducted to identify the influence of the inflation rate in deviating the machinery hire which results in cost overrun. Also, the interconnectivity of machinery hire rates was evaluated through the correlation coefficient. The analysis shows that the inflation rate possesses a weak relationship with nine and a moderate relationship with five machinery hire rates. However, the interconnectivity of the machinery hire rates was strongly correlated with each other, which emphasize that a change due to the influential factor will affect all the rates and can cause cost overrun. It is therefore recommended to observe other factors which deviate the machinery hire rates within the construction industry. Â© 2021. All Rights Reserved.